Addressing the challenges of intellectual disability identification for health policy and research in Australia - Leonard, Helen; Wong, Kingsley; Liao, Peiwen; Khan, Manzoor; Aitken, Zoe; Bourke, Jenny; Trollor, Julian N.; Downs, Jenny; O’Donovan, Mary-Ann; Kavanagh, Anne M.; Srasuebkul, Preeyaporn (Frontiers in Psychiatry, 2026)
This article discusses the important issue of the need for a stable definition of intellectual disability in order to allow comparisons by place and over time such as in the monitoring of this population’s health needs and utilization. The aim of the new Australian National Centre for Intellectual Disability Health, established in 2023, is to ensure that all Australian children and adults with intellectual disability receive high-quality healthcare that meets their needs. Monitoring changes in this regard requires accurate identification of the number of people with intellectual disability within a population which itself is inherently dependent on how intellectual disability is defined. We have used a definition which is relatively easy to operationalize through different sources i.e. a full-scale IQ of less than 70, a condition known to be consistent with intellectual disability or documentation of intellectual disability in medical records; through education a level of intellectual disability defined as either mild/moderate or greater, and through the National Disability Insurance Scheme an International Classification of Diseases (ICD-10-CM) diagnostic code associated with intellectual disability. In contrast the definition required by Inclusion Australia “a lifelong condition that affects a person’s intellectual skills and their behavior in different situations” is much more difficult to operationalize. We discuss this challenge within the context of historical changes and the range of sources possibly able to provide this information today. We present two case studies from different Australian states and conclude with some suggestions for a multi-source approach using data linkage.